Les féminins conjugaux en français, ou la langue fonctionnant sans entrave - Thomas Linard (Glad!)
The subject of matrimonial feminine in French has already been treated by several studies, but always with the idea of going beyond them, to arrive at the real subject : professional feminine. This research note, a result of lexicographical work on more than 200 matrimonial feminines in French, intends to show that the two categories, matrimonial and professional feminines, are not to be opposed, and that in fact, matrimonial feminines reflect a time when feminization took place without extralinguistic obstacles : in this way, they are useful for shedding light on the present.